2010
DOI: 10.1093/pasj/62.6.1525
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Period Variations of Superhumps in SU UMa-Type Dwarf Novae. II The Second Year (2009–2010)

Abstract: Continued from Kato et al. (2009, PASJ, 61, S395), we collected the times of superhump maxima for 68 SU UMa-type dwarf novae, mainly observed during the 2009–2010 season. The newly obtained data confirmed the basic findings reported in Kato et al. (ibid.): the presence of stages A–C and the predominance of positive period derivatives during stage B in systems with superhump periods shorter than 0.07 d. There was a systematic difference in the period derivatives for the systems with superhump periods longer tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Savoury et al 2011), new potential calibration systems have emerged, in addition to revised q values for existing calibration systems. Revised superhump periods have also been measured, courtesy of the SU UMa-type DNe survey of Kato et al (2009Kato et al ( , 2010Kato et al ( , 2012Kato et al ( , 2013Kato et al ( , 2014aKato et al ( ,b, 2015Kato et al ( , 2016Kato et al ( , 2017. With all of these new measurements becoming available since the work of Knigge (2006), it is appropriate to update the calibration of the (q) relation.…”
Section: Updating the Calibration Of The Superhump Period Excess-massmentioning
confidence: 99%
See 1 more Smart Citation
“…Savoury et al 2011), new potential calibration systems have emerged, in addition to revised q values for existing calibration systems. Revised superhump periods have also been measured, courtesy of the SU UMa-type DNe survey of Kato et al (2009Kato et al ( , 2010Kato et al ( , 2012Kato et al ( , 2013Kato et al ( , 2014aKato et al ( ,b, 2015Kato et al ( , 2016Kato et al ( , 2017. With all of these new measurements becoming available since the work of Knigge (2006), it is appropriate to update the calibration of the (q) relation.…”
Section: Updating the Calibration Of The Superhump Period Excess-massmentioning
confidence: 99%
“…Given our updating of the superhump-mass ratio relations above, we revisit the analysis of donor star properties in Knigge (2006) and Knigge et al (2011). Firstly, P sh values for all SU UMa-type DNe in the Patterson et al (2005) sample (70 systems) were replaced by P B sh measurements from the SU UMa-type DNe survey of Kato et al (2009Kato et al ( , 2010Kato et al ( , 2012Kato et al ( , 2013Kato et al ( , 2014aKato et al ( ,b, 2015Kato et al ( , 2016Kato et al ( , 2017. For a number of systems, P orb was also updated, either from measurements made by Tables 2 and B1 Patterson et al (2005).…”
Section: Donor Masses and Radii Of Superhumping Cvsmentioning
confidence: 99%
“…This is not surprising, since spectroscopy of fainter targets can be very difficult. It is fortunate, then, that many of the shortest-period CVs undergo superoutbusts and show superhumps, which can be used to derive approximate periods that are good enough for many purposes (see, e.g.. Kato et al 2009Kato et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…When Szkody et al (2006) performed follow-up photometry on this object, they found it in outburst and discovered a 1.58 hr superhump modulation, implying an orbital period near 91 minutes. Kato et al (2010) report P sh = 93.54(4) minutes early in the outburst, increasing to 93.91(4) minutes later. Our spectroscopic orbital period is 90.86(13) minutes, so that…”
Section: Sdss J16539+2010 = V1227 Hermentioning
confidence: 92%
“…We used the phase dispersion minimization (PDM, Stellingwerf 1978) method to identify periods in the data. The error of the PDM analysis was estimated by the methods of Fernie (1989) and Kato et al (2010). Although we also applied the least absolute shrinkage and selection operator (Lasso) method (Tibshirani 1996;Kato and Uemura 2012) particularly using the two-dimensional version (Kato and Maehara 2013), we do show the result since we could not find particular advantage over the PDM method.…”
Section: Observation and Analysismentioning
confidence: 99%